Recent Advances in Hollow Gold Nanostructures for Biomedical Applications - Park, Jeong-Min; Choi, Hye Eun; Kudaibergen, Dauletkerey; Kim, Jae-Hyuk; Kim, Ki Su (Frontiers in Chemistry, 2021)
The localized surface plasmon resonance of metallic nanoparticles has attracted much attention owing to its unique characteristics, including the enhancement of signals in sensors and photothermal effects. In particular, hollow gold nanostructures are highly promising for practical applications, with significant advantages being found in their material properties and structures: 1) the interaction between the outer surface plasmon mode and inner cavity mode leads to a greater resonance, allowing it to absorb near-infrared light, which can readily penetrate tissue; 2) it has anti-corrosiveness and good biocompatibility, which makes it suitable for biomedical applications; 3) it shows a reduced net density and large surface area, allowing the possibility of nanocarriers for drug delivery. In this review, we present information on the classification, characteristics, and synthetic methods of hollow gold nanostructures; discuss the recent advances in hollow gold nanostructures in biomedical applications, including biosensing, bioimaging, photothermal therapy, and drug delivery; and report on the existing challenges and prospects for hollow gold nanostructures.